An Analytical Study of Exercises in Secondary English Textbooks published by NCERT with reference to Revised Bloom’s Taxonomy - Lalchhandami, Sian; Malsawmi, H. (JOURNAL OF INDIAN EDUCATION, 2021)
The present study analyses the exercises found in the NCERT English textbooks for secondary school students based on the Revised Bloom’s Taxonomy (RBT). The sample of the study consisted of 1119 end-of-chapter exercises in Class IX and Class X English textbooks. A study analysis sheet was prepared and used for classification of the questions in both the cognitive process and knowledge dimensions. The results revealed the following: most of the questions (74.14%) were within the first two levels—remembering (26.27%) and understanding (47.90%), which reflected the preponderance of lower level questions in the investigated textbooks. The study also found the dominance of exercises testing factual knowledge (61.40%) in the knowledge dimension of the RBT. Based on the findings it is recommended that textbook writers and educators include higher order questions within curriculum and pedagogy to help improve critical thinking among learners.